INTERACTION OF SOWING DEPTH AND TYPE OF SEED GERMINATION - HYPOGEAL OR EPIGEAL - ON THE GERMINATIVE PERFORMANCE OF SOYBEAN AND PIGEON PEA SEEDS - VAZQUEZ, G. H.; SOUZA, W. J. O. DE; VANZELA, L. S.; ISA, K. M.; ASSIS, A. V. DE (Revista Brasileira de Engenharia de Biossistemas, 2011)
The objective of this experiment was to evaluate how the type of seed germination – the hypogeal (pigeonpea) and the epigeal (soybean) germinations - interferes on seed germinative performance when these seeds are sown at different depth (3, 6, 9, and 12 cm). In increased depths up to 7 cm, seeds of the hypogeal and the epigeal germination undergo growing and equivalent losses in their capacity to germinate and to result in seedlings capable of emerging above soil surface. When sowing depth is bigger than 7 cm, the epigeal germination is more hampered than the hypogeal one, reducing the height, the percentage and speed of seedling emergence. Pigeonpea seeds germination is not significantly affected by global densities up to 1.6 g cm-3.